Water–energy–carbon nexus of different land use types: The case of Zhengzhou, China - Mengyu Feng; Rongqin Zhao; Huiping Huang; Liangang Xiao; Zhixiang Xie; Linjing Zhang; Jin Sun; Xiaowei Chuai (Ecological Indicators, 2022)
The rapid urban expansion of China has led to a large amount of water and energy consumption, and caused drastic growth of carbon emissions. Discovering the water–energy–carbon nexus of different land use types helps explain the interactions between resources capacity and environmental effects of land use activities, as well as provides reasonable options for land use management based on water–energy conservation and carbon emission reduction. In this paper, carbon emission/absorption of different land use types was estimated and the water–energy–carbon nexus of different land use types in Zhengzhou was analyzed. Through the SD model, the future carbon emissions of different scenarios were predicted under water, energy, and land constraints. It showed that total carbon emission increased and carbon absorption reduced along with the land use change during the rapid urbanization process of Zhengzhou city. The water and energy consumption and carbon emissions of different land use types were determined by the different intensities and their spatial patterns of human activities. Therefore, carbon emission and its intensity varied with land use types and water–energy–carbon nexus was closely related to land use types. The carbon emission prediction showed that the carbon emission reduction potential was the highest and the peak carbon emission (40.18 × 106 t) occurred in 2025 under a comprehensive scenario, which was designed with water–energy saving and optimization of land use structure. This study could provide references for policy–makers to formulate differentiated strategies for different land use activities, and contribute to realize water–energy saving and efficient utilization of land and the emission reduction of Zhengzhou city.